The hudoq mask works potential as a source of learning and moral based local wisdom of Dayak bahau busang tribe - Jesita Trisnawati; Syakir Muharar; Eko Sugiarto (Trigin Publisher, 2023)
The Hudoq mask is a dance attribute used in the Hudoq ritual ceremony in Ujoh Bilang Village, Long Bagun District, Mahakam Ulu Regency. This research uses descriptive analysis method, using data collection techniques; observation techniques, interview techniques, and documentation. This study aims to describe and analyze cultural values, and their potential as a source of learning and morals based on local wisdom contained in the Hudoq mask dish. Topeng Hudoq is a regional art that must be maintained and preserved in society, especially in the younger generation, because regional art is an asset and cultural identity of the Dayak Bahau Busang Tribe. The wisdom values contained in the Hudoq mask art are religious values, cultural values, moral values, aesthetic values, togetherness values, politeness values, and social values. The Hudoq mask has the potential to become a source of learning about fine arts and morals because it has unique shapes and motifs that can be used as a source of learning about fine arts, namely drawing. Training children to draw with objects that are close to the environment in which they live is related to culture, can instill a sense of love for culture in children as well as education of cultural values, and aims to teach lessons that customs need to be maintained and maintained. preserved for future generations.